ETHNOPHARMACOLOGICAL ANALYSIS OF MEDICINAL PLANTS IN A QUILOMBOLA COMMUNITY: EMPHASIS ON CHRONIC DISEASES - Santos, Thais Gomes dos; Amaral, Raquel Rodrigues do; Vieitas, Diurieny Ribeiro Itaparica; Monteiro Neto, Moacir de Azevedo Bentes (Cogitare Enfermagem, 2023)
Objective: To understand the ethnopharmacological knowledge of medicinal plants used to treat chronic diseases in a quilombola community in the Brazilian Amazon. Method: A cross-sectional, descriptive study using a semi-structured questionnaire in a quilombola community in Macapá, Amapá (Brazil), from March to June 2022. The analysis was carried out using descriptive statistics. Results: In the quilombola community, women are the main holders of knowledge about medicinal plants, usually acquired from their parents/grandparents. Among the various plants mentioned, boldo was the most frequently mentioned (13.78%) for treating liver diseases, followed by mastruz (6.89%) for inflammatory issues. Conclusion: The study's results made it possible to understand the ethnopharmacological knowledge of phytotherapy in treating chronic non-communicable diseases and how it can act in an alternative and positive way in the clinical manifestations or complications caused by these diseases.